Umbilical Cord Care Effectiveness Closed and Open To Release Cord Newborn - Risa Pitriani; Ika Putri Darmayanti; Rita Afni (Jurnal Doppler, 2017)
Cause of early neonatal death was infection by (57.1%). The infection is neonatal tetanus were disebebkana by cord care that is not true and sterile. The research goal is to determine the level of effectiveness of Umbilical Cord Care Closed And Open With Release of Newborn Umbilical Cord. This research was conducted in Puskesmas Rumbai Coastal. The population in this study were all newborns (age 0Ë—14 days) in the month of February to April 2015. The sample in this study were all infants (aged 0Ë—14 day) were born in February-April 2015 as many as 32 people. This type of research is true experimental design (pure experimentation) with a kind of post test only control design. The analysis used is the analysis of univariate and bivariate. From the statistical test showed that variants of two groups of P Value 0.169> 0.05, which means that the variance of the two groups are the same. P Value T test Test we can see that P Value 0.000 <0.05, which means that there is a significant difference between open and cord care umbilical cord care covered by the release cord. Health workers are expected to do counseling or training about cord care closed and open so that the cord separated in time and reduces the occurrence of infection in the baby's umbilical cord.